2019
DOI: 10.1088/2053-1583/ab4ef3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-terminal electronic transport in boron nitride encapsulated TiS3 nanosheets

Abstract: We have studied electrical transport as a function of carrier density, temperature and bias in multiterminal devices consisting of hexagonal boron nitride (h-BN) encapsulated titanium trisulfide (TiS3) sheets. Through the encapsulation with h-BN, we observe metallic behavior and high electron mobilities. Below ∼60 K an increase in the resistance, and non-linear transport with plateau-like features in the differential resistance are present, in line with the expected charge density wave (CDW) formation. Importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It is worth pointing out that a theoretical study of the injection of carriers through electric field gating in single layers of TiS 3 , where electrons are injected into the same type of band that we are discussing, indeed predicted the possibility of CDW-type anomalies . Later, experimental work reported transport measurements suggesting CDW formation, although a more complete characterization is still needed. …”
Section: Results and Discussionmentioning
confidence: 63%
“…It is worth pointing out that a theoretical study of the injection of carriers through electric field gating in single layers of TiS 3 , where electrons are injected into the same type of band that we are discussing, indeed predicted the possibility of CDW-type anomalies . Later, experimental work reported transport measurements suggesting CDW formation, although a more complete characterization is still needed. …”
Section: Results and Discussionmentioning
confidence: 63%
“…Our argument is based on the data given by Lipatov et al [43] who reported mobilities of nanowhiskers between 18 and 24 cm 2 /(V·s) on Si/SiO 2 at room temperature, which increase up to 43 cm 2 /(V·s) on Al 2 O 3 . Recent data by Papadopoulos et al contain measurements of around 250 cm 2 /(V·s) encapsulated in hexagonal boron nitride (hBN) at 90 K [44]. Deposited samples of graphene [45] and MoS 2 [46] on this material showed comparable mobilities as those of Table 1.…”
Section: Electron Mobilitiesmentioning
confidence: 79%
“…Layered TiS 3 has a similar band gap width to silicon (about 1 eV) and theoretical electronic mobility of up to 10,000 cm 2 V –1 s –1 , making it have great potential as a substitute for silicon . So far, the synthesis of TiS 3 mainly includes chemical vapor transport (CVT), mechanical exfoliation, and a solution synthesis method. Due to the long reaction time, the growth of TiS 3 is often conducted in a low-pressure sealed ampoule. Shkvarin et al used titanium disulfide (TiS 2 ) and sulfur (S) as precursors to react in the ampoule for a week, and then the TiS 3 crystal appeared at the medial of the ampoule after cooling down.…”
Section: Introductionmentioning
confidence: 99%